A Comparison of two logistic systems in the UK and China Frozen Food Industries - Cheung, Michael HoYin (2006)
This purpose of the dissertation was to compare two logistics system, where one is located in the United Kingdom and the other in China. What was discovered from this investigation was although Birds Eye has a more developed logistics systems there are still certain problems that exists and certain areas that are needed for improvement. These were concluded to be, more integration on the information system to produce a more live feed on information and to combat the problem on traffic congestion on the road networks.